The Effect of Good Corporate Governance, Gender Diversity and Age Diversity on Financial Performance in Infrastructure Sector Companies Listed on The Indonesia Stock Exchange in 2020-2023 - Rizki Ghina Izdihar; Ilham Wahyudi; Muhammad Gowon (Green Economics: International Journal of Islamic and Economic Education, 2025)
This study aims to find out and prove the influence of Good Corporate Governance, Gender Diversity, and Age diversity on financial performance in infrastructure sector companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The companies that became the population in this study were 69 companies by eliminating as many as 23 companies. The analysis methods used in this study are classical assumption tests, multiple linear regression analysis, and hypothesis testing using SPSSV26 For Windows software as a tool. The results of this study stated that the audit committee, institutional ownership, gender diversity of the board of commissioners, age diversity of the board of commissioners had no effect on financial performance. Gender diversity of the board of directors and gender diversity of the board of directors have an impact on financial performance.